PENGARUH BONDING AGENT DAN SERAT GELAS PADA PAPAN SEMEN RINGAN - Irfan Oktariadi Oktariadi; Pratikto; Anni Susilowati (Universitas Widyatama, 2022)
A ceiling is a building material that is inseparable from a building. The material for the ceiling must be flexible, light, durable, and easy to install. So that the weight of the cement board is light, foam is used as its constituent material. Due to the weak flexural strength of foam mortar, an alternative that can be taken is to add glass fiber and a bonding agent to the lightly foamed cement board mix. This study aims to obtain physical and mechanical properties as well as optimum levels of fiberglass and bonding agent to achieve maximum flexural strength. The board is made from a mixture of PC, sand, water, fiberglass, foam agent and bonding agent. The mixture ratio used is 1 Cement : 1,2 Sand : 0.15 phase, foam agent 1:30 and 5 different variations of glass fiber, namely 0, 3, 6, 9 and 13%. For density and specific gravity values, the tendency is decreasing, while for the ability to nail variations of 0 and 3% experiencing cracks and splits, the shape test is in accordance with the requirements of SNI. As for thickness expansion, moisture content, water absorption and flexural strength tend to increase. Based on the test results, the optimum level of use of glass fiber and bonding agent on lightweight cement boards is 6% fiber variation because it has the highest flexural strength value of 33.07 kg/cm².